Hepatitis B Treatment with Acupuncture and Herbal Medicine - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (European Scientific Journal, ESJ, 2018)
Hepatitis B is liver inflammation caused by the hepatitis B virus (HBV). HBV infection causes an acute illness that may end up in curing the patient or becoming a chronic illness that progresses to serious liver damage. The treated patient is a 33 year old woman, diagnosed with multiple conditions, but the main treatment was made to correct the hepatitis B infection and the secondary complications – ascites, liver cirrhosis, thrombocytosis, splenomegaly and hepatic vein thrombosis (Budd-Chiari Syndrome). The patient was also diagnosed with primary hypothyroidism. Beside the prescribed medications and hormone therapy, the patient was treated with acupuncture and herbal treatment. In the herbal treatment were used two funguses in capsules - Cordyceps sinensis 1.5g per day and Ganoderma lucidum 3g per day. In the acupuncture treatment were used the points located on the meridians of Spleen, Liver, Stomach, Dumai and Renmai. The patient has made 10 acupuncture treatments, once weekly in a period of three months, combined with herbal treatment. After the treatment the patient felt better, the accompanied symptoms were gone and the blood test results were significantly improved. The patient is in good health condition now, however the herbal treatment will continue for prevention and future follow-up will be done in this case.